Improved Integration Services In LRT Mode, BRT Trans Musi And River Transport In Palembang - Wiratman, Andi; Muthohar, Imam; Wibisono, Bambang Hari (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
Ampera Light Rail Transit Station (LRT) in Palembang, located close to the BRT Trans Musi stop, and River Transport Pier. But the problem that arises is that the 3 modes are not yet integrated so that passengers still have difficulty switching modes quickly, easily and safely and don't yet have payment facilities (ticketing), namely one payment access for multimodal (smart cards). The purpose of this study was to determine passenger perceptions about the physical integration facilities of passengers and the payment integration system (ticketing) when they were going to switch modes that would be used as a reference in the form of a design of physical integration facilities and ticketing. The analytical method used is the IPA (Importance Performance Analysis), the results of interviews with informants and the results of observations in the fields that will be a reference in making design forms so that they can answer the problem. The results showed that according to passenger perceptions there were 19 service attributes that had low performance so improvements had to be made. The results of interviews with several informants concluded that in the Ampera LRT Station area needs to be improvement and improvement intermodal physical integration facilities, with the form of facilities namely eleveted corridors (sky bridge), not eleveted, closed, safe, comfortable, fast, and can accommodate disabilities.